Jesus Cristo Senhor e Salvador da Cidade - Imaginário Crente e Utopia Política - Clara Mafra (Universidade do Estado do Rio de Janeiro, 2006)
The author discusses a municipal ordinance signed by the obscure mayor of a town in Rondônia State, Brazil, whereby he declares Jesus Christ the town's only Lord and Savior, in order to explain some of the tensions experienced by a country with a Republican political system undergoing the expansion of its democratic life. The argument is that the mayor, like more and more contemporary citizens, accesses the foundations for exercising the Republic without necessarily knowing their internal logical or historical development. On the other hand, neophytes grasp the Republican armamentarium with a vague and indeterminate meaning that is filled according to an imagination shaped by embodied skills.